2015
DOI: 10.1136/emermed-2014-204426
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in medical patients seeking ED care for somatic reasons: results of a systematic literature review

Abstract: There is strong evidence that psychological distress is an important and prevalent cofactor in medically ill patients presenting to the ED with harmful associations with (subjective) health outcomes. To prove causality, future research should investigate whether screening and lowering psychological distress with specific interventions would result in better patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…We have also reviewed previous studies that used validated instruments to measure distress in ED patients in a systematic research [25]. We found that most instruments used have been focused on depressive symptoms neglecting all other affective dimensions of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…We have also reviewed previous studies that used validated instruments to measure distress in ED patients in a systematic research [25]. We found that most instruments used have been focused on depressive symptoms neglecting all other affective dimensions of psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is confronted with reports that there is a significant increment in the number of patients with psychological problems reported to EDs. Previous reports showed that psychological distress is present in 84% of patients who had frequent attendance to EDs [4,5]. This has raised the attention toward the need to address the knowledge and skills of nursesat the emergency departments where specialized psychiatric personnel are present to provide appropriate psychological intervention once needed.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients experience psychological distress as somatic symptoms such as headaches, sleeping problems, and gastrointestinal symptoms and seek medical help for these issues. [18][19][20][21][22] Research has suggested that patients with a background of psychological problems contact their general practitioner (GP) nearly twice as often for both psychological and somatic symptoms compared with patients without a background of psychological problems. 23 Evidence has demonstrated that integrated psychosocial care, which combines psychological screening and psychological interventions, is an effective means of treating psychological distress.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological distress includes persistent levels of anxiety, depressive feelings, and fears, and has a great impact on a patient's daily life. Some patients experience psychological distress as somatic symptoms such as headaches, sleeping problems, and gastrointestinal symptoms and seek medical help for these issues . Research has suggested that patients with a background of psychological problems contact their general practitioner (GP) nearly twice as often for both psychological and somatic symptoms compared with patients without a background of psychological problems .…”
Section: Introductionmentioning
confidence: 99%